HISTOMORPHOMETRICAL EVALUATION IN TESTIS AND EPIDIDYMIS OF RATS WITH PULMONARY EMPHYSEMA EXPERIMENTALLY INDUCED BY PROLONGED EXPOSURE TO CIGARETTE SMOKE - Ribeiro, Amanda de Genova [UNESP]; Ribeiro-Paes, Joao Tadeu [UNESP]; Stessuk, Talita; Kozma, Rodrigo de Las Heras; Cherici Camargo, Isabel Cristina [UNESP] (Univ Federal Uberlandia, 2016)
The study evaluated the histomorphometrical aspects of testis and epididymis of adult rats with pulmonary emphysema experimentally induced by exposure to cigarette smoke for 30 weeks. Previous studies related to effects of the cigarette smoke on male reproductive tissue were performed in relatively shorter time periods and thus, it does not allow a direct correlation between smoke exposure and damage to reproductive structures like testis and epididymis. In order to evaluate the effect of cigarette smoke for long period on the testis and epididymis, twelve adult Wistar rats were divided into two groups: Control (CG; exposed to ambient air) and Smoking (SG; exposed to cigarette smoke). The weight of the testes, epididymides, seminal glands and prostate were not affected (p>0.05) by experimental treatment. In the SG, the testes presented cellular desquamation, significant decrease in the number of germ cells and Sertoli cell, and reduction (p<0.05) in area and diameter of seminiferous tubules. The exposure of animals to cigarette smoke did not promoted histological changes in the epididymis, but decreased significantly the ductular area and epithelial height in the caput and corpus regions. It was concluded that testis was more susceptible than the epididymis to the effects of cigarette smoke constituents in rats with pulmonary emphysema experimentally induced by prolonged cigarette-smoke exposure.
Keywords: Tobacco; Reproductive toxicology; Pulmonary emphysema; Comorbities